Taxonomic delimitation of Arbutus mollis and A. occidentalis (Ericaceae) - González-Elizondo, M. Socorro; González-Elizondo, Martha; Zamudio, Sergio (Instituto de Ecología, A.C., 2022)
Arbutus mollis Kunth in H.B.K. treated since long ago as a synonym of A. xalapensis Kunth in H.B.K. is the correct name for the plants formerly treated as A. occidentalis var. villosa McVaugh & Rosatti. A revision of the complex of A. occidentalis McVaugh & Rosatti reveals that the two varieties originally described for that species differ in characters of foliage, indument and inflorescence, which suggests an origin from different lineages and justify their separation to the species level, and therefore A. mollis is recognized here as an independent species. The shrubby habit shared by A. mollis and A. occidentalis is probably a case of convergent evolution. The taxonomic reinstatement of A. mollis is made and amended descriptions for A. mollis and A. occidentalis and a key to distinguish them are given. Apparent intermediates are either morphs, hybrids, stump sprouts of tree species after fire or cutting, or rarely shrubby forms of other species. The following hybrids are documented: Arbutus mollis x A. tessellata (Guanajuato and Michoacán), Arbutus mollis x A. xalapensis (Querétaro), Arbutus occidentalis x A. arizonica (Durango, Aguascalientes, and Jalisco), Arbutus occidentalis x A. tessellata (Jalisco), Arbutus occidentalis x Arbutus bicolor (Chihuahua and Durango), and Arbutus occidentalis x Arbutus aff. xalapensis (Durango and Jalisco).